2006
DOI: 10.1021/ol0529593
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Silanes via Asymmetric Hydrosilylation with Catalytic CuH

Abstract: [reaction: see text] CuH-catalyzed asymmetric conjugate reduction of beta-silyl-alpha,beta-unsaturated esters has been developed. Using PMHS as a stoichiometric source of hydride and in situ generated CuH ligated by Solvias' JOSIPHOS analogue PPF-P(t-Bu)(2) leads to highly enantioselective 1,4-reductions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 24 publications
0
17
0
3
Order By: Relevance
“…For example, we have previously demonstrated that nonracemically ligated copper hydride can reduce E or Z b-silylenoates to afford chiral bsilanes with excellent enantioselectivity. [31] Alternatively, these substrates can be used to construct stereochemically pure vinyl iodides. DIBAL-H reduction of 12 afforded the corresponding b-silyl allylic alcohol (82 %; Scheme 5).…”
Section: Methodsmentioning
confidence: 99%
“…For example, we have previously demonstrated that nonracemically ligated copper hydride can reduce E or Z b-silylenoates to afford chiral bsilanes with excellent enantioselectivity. [31] Alternatively, these substrates can be used to construct stereochemically pure vinyl iodides. DIBAL-H reduction of 12 afforded the corresponding b-silyl allylic alcohol (82 %; Scheme 5).…”
Section: Methodsmentioning
confidence: 99%
“…These approaches, however, rely on the more established rhodiumcatalyzed enantioselective formation of CÀC bonds [11] (C!A, Scheme 1) and copper-catalyzed enantioselective formation of CÀH bonds [12] (D!A, Scheme 1).…”
mentioning
confidence: 99%
“…By contrast, the SEGPHOS analogue (184) gave inferior results. 233 A highly enantioselective synthesis of α-dehydroamino acids (186) with a stereogenic centre at the γ -position has been developed, which employs a copper-catalysed ee asymmetric conjugate addition of diethylzinc to α,β-unsaturated imines (185) with the TADDOL-derived phosphoramidite (187) as a chiral ligand. 234 The reaction of allyl carbamates (189) with activated enones (188) catalysed by (Ph 3 P) 4 Pd in THF proceeded smoothly at room temperature to give the corresponding α,β-bis-adducts (190) in high yields.…”
Section: Mementioning
confidence: 99%